PEMBINAAN AKHLAK PESERTA DIDIK DI SD RUNIAH SCHOOL MAKASSAR - Rahman, Fahrul; Amri, Muhammad; Rasyid, Muhammad Nur Akbar (Istiqra: jurnal hasil penelitian, 2023)
The position of morals in people’s lives occupies an important position, because the rise and fall of a society depends on the morals it has, if its morals are good, then its inner and outer prosperity will be. However, if morals are damaged, people’s lives will also be damaged. This research aims to explain moral development at SD Runiah School Makassar such as habituation, teacher example and giving advice to students. This research includes qualitative descriptive research, with a phenomenological approach. The data collection methods in this research used observation, interviews and documentation methods. The data analysis techniques used are data reduction, data display and conclusion drawing. Meanwhile, the test for the validity of the data used is the degree of trust (credibility). The results of this research show that the habituation at SD Runiah School Makassar is to get students used to doing positive things both inside and outside the classroom. Then the teacher’s example for students at SD Runiah School Makassar is greeting students, carrying out congregational prayers, and so on. Furthermore, giving advice at SD Runiah School Makassar is giving advice to students inside and outside the classroom in the form of meaningful advice.